2022
DOI: 10.1038/s41556-022-00974-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two pathways mediating protein targeting from ER to lipid droplets

Abstract: Pathways localizing proteins to their sites of action are essential for eukaryotic cell organization and function. Although mechanisms of protein targeting to many organelles have been defined, how proteins, such as metabolic enzymes, target from the endoplasmic reticulum (ER) to cellular lipid droplets (LDs) is poorly understood. Here we identify two distinct pathways for ER-to-LD protein targeting: early targeting at LD formation sites during formation, and late targeting to mature LDs after their formation.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 87 publications
3
46
0
Order By: Relevance
“…After avoiding translocation, APOE traffics to LDs from the cytoplasmic surface of the ER via membrane bridges. Recent study of the mechanism of protein trafficking from the ER to LDs identified both "early" and "late" ER to LD (ERTOLD) pathways (Song et al, 2022). Given that we observe APOE coating LDs several hours into OA treatment, we hypothesize that it may move onto LDs via the "late" pathway.…”
Section: Discussionmentioning
confidence: 72%
“…After avoiding translocation, APOE traffics to LDs from the cytoplasmic surface of the ER via membrane bridges. Recent study of the mechanism of protein trafficking from the ER to LDs identified both "early" and "late" ER to LD (ERTOLD) pathways (Song et al, 2022). Given that we observe APOE coating LDs several hours into OA treatment, we hypothesize that it may move onto LDs via the "late" pathway.…”
Section: Discussionmentioning
confidence: 72%
“…These ER-LD connections facilitate the exchange of proteins and lipids between the two compartments. It is believed that this transport occurs through membrane continuity, so the dual location strategy of LDs and ER may be a more effective choice when using compartmentalization strategies to increase metabolite flux (Figure b,c). Guo et al divided the ER-located enzymes in the 7-dehydrocholesterol (7-DHC) synthetic pathway into four modules and then targeted modules ERG25/26/27 and ERG2/3 into LDs to promote the conversion efficiency of sterol intermediates to 7-DHC by using the dual localization of ER and LDs …”
Section: Designing Intracellular Compartments Based On Natural Subcel...mentioning
confidence: 99%
“…However, we have not examined the lipid exchange between the cell membrane and LDs due to technical obstacles. A recent genome wide RNA interference (RNAi) screen using Drosophila cells has identi ed multiple players in targeting proteins from the endoplasmic reticulum to LDs, both during the early phase at LD formation sites and late stage targeting to mature LDs (Song et al, 2022). Further study is necessary to fully understand mechanisms controlling LD metabolism.…”
Section: Limitations Of the Studymentioning
confidence: 99%